Perspectives for Cosmological Reionization From Future CMB and Radio Projects - Trombetti, Tiziana; Burigana, Carlo (Frontiers in Astronomy and Space Sciences, 2018)
In spite of the great recent results from the Planck satellite supporting cosmological reionization scenarios almost compatible with astrophysical models for the evolution of structure, galaxy and star formation, the full understanding of the reionization and thermal history since recombination epoch is still far to be consolidated. The radio to sub-millimeter background provides a very important window for studying cosmological reionization process in a global approach, to arrive to the complete comprehension of the involved photon and energy sources. CMB polarization provides global information of ionization history, 21-cm line tomographic view allows to reconstruct ionization and clumping history, CMB spectral distortion provides global information on these aspects and a direct view of the global energy dissipations. Given the relevance of cosmological reionization for the comprehension of early phases of structure formation and evolution and its connection with a large variety of astrophysical and cosmological questions, it is important to discriminate among the various models compatible with current data. A brief overview of the proposals of future CMB missions and of radio [namely the Square Kilometer Array (SKA) and its precursor/pathfinders] projects is presented. We then describe the scientific outcome of future CMB missions, focussing on the information carried out by polarization anisotropies, spectral (absolute temperature) distortion and dipole (anisotroy) distortions, and discuss the promising perspectives opened by forthcoming and future radio surveys, focussing on the information carried out by the redshifted 21-cm line and by the free-free diffuse emission. Finally, we describe the contribution of future radio surveys to reionization studies with CMB polarization projects.